2012
DOI: 10.1002/ccd.23100
|View full text |Cite
|
Sign up to set email alerts
|

Early‐ and mid‐term outcomes of transcatheter aortic valve implantation in patients with logistic EuroSCORE less than 20%: A comparative analysis between different risk strata

Abstract: This study tends to suggest that current mortality reported after TAVI could be significantly affected by the very-high risk profile of the population which currently undergoes this procedure, making comparison with surgical series rather unreliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The patients had mean EuroScore of 39.30% and mean STS score of 30.28%, which means that higher mortality rates than the ones described in major studies worldwide [20][21][22][23][24][25][26] can be explained by greater patient severity. A recent study in Italy [29] evaluated 165 patients who had undergone transcatheter aortic valve implantation. They were grouped according to EuroScore, above or below 20%.…”
Section: Discussionmentioning
confidence: 99%
“…The patients had mean EuroScore of 39.30% and mean STS score of 30.28%, which means that higher mortality rates than the ones described in major studies worldwide [20][21][22][23][24][25][26] can be explained by greater patient severity. A recent study in Italy [29] evaluated 165 patients who had undergone transcatheter aortic valve implantation. They were grouped according to EuroScore, above or below 20%.…”
Section: Discussionmentioning
confidence: 99%
“…In the multicentre United States registry cited above, 1-year mortality among inoperable patients was 24.3% [23]. Tamburino et al [10] found that at 1 year after TAVI, mortality in the log ES ≥ 20% group was 25.7% compared to 6.8% in the log ES < 20% group. In the study by Wenaweser et al [13], mortality at 1 year was 10.1% vs. 16.1% vs. 34.5%, respectively, in patients with STS score risk of < 3%, 3-8%, and > 8%.…”
Section: Long-term Outcomesmentioning
confidence: 97%
“…In several studies that included moderate risk patients, an association between log ES and 30-day mortality was found. In a study in 165 patients, Tamburino et al [10] found that 30-day mortality after TAVI was 15.6% in those with log ES ≥ 20% but much lower (2.4%) in those with log ES < 20%. Similar results were reported by Wenaweser et al [13] who divided 389 patients treated with TAVI into three groups depending on the operative risk by the STS risk score: low risk patients with STS < 3%, moderate risk patients with STS 3-8%, and high risk patients with STS > 8%.…”
Section: Immediate Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…Tamburino et al 120 found that the outcome of patients, principally treated with a CoreValve, who were at lower risk (logistic EuroSCORE [LES] <20%), is better than those at higher risk (30-day and 1-year mortality rate, 2.4% and 6.8% versus 15.6% and 25.7%). The rate of major adverse cardiovascular events was also lower at 30 days (6% versus 20.8%) and at 1 year (11.4% versus 27.1%).…”
Section: Other Observational Datamentioning
confidence: 99%